Angiographic analysis on posterior fossa hemorrhages and vascular malformations beyond aneurysms by CT angiography and digital subtraction angiography - S. Vignesh; Surya Nandan Prasad; Vivek Singh; Zafar Neyaz; R. V. Phadke; Anant Mehrotra; Prabhakar Mishra (Egyptian Journal of Neurosurgery, 2022)
Abstract Background Posterior fossa malformations are less common than supratentorial malformations, but hemorrhages in posterior fossa are more serious due to presence of vital structures within this region. Most common cause of bleed in posterior fossa apart from hypertension is aneurysms but other vascular malformations are also there which cause hemorrhage. Here we discuss other causes of posterior fossa bleed beyond aneurysms. Results A total of 80 patients were evaluated: 47 (58.8%) had aneurysms, 29 (36.3%) had arteriovenous malformations, one each had developmental venous anomaly and brainstem cavernoma. Thirty vascular malformations were detected, of which 18 (62.1%) were pial arteriovenous malformations (AVMs), 11 (37.9%) were dural arteriovenous fistulas (dAVF), and one had developmental venous anomaly (DVA). Six patients of AVM underwent both DSA and CTA, and CTA could correctly diagnose only 2 of 4 pial AVMs detected by DSA. Among two dAVFs detected by DSA, CTA could demonstrate dAVF only in one patient. Conclusion CTA could be used as alternative to DSA in diagnosis and characterizing aneurysms in posterior fossa but for AVMs, 3D-CTA cannot replace DSA; however potential of time-resolved CTA (TR-CTA) appears promising.